Biomimetic intrafibrillar silicification of collagen fibrils through a one-step collagen self-assembly/silicification approach. Issue 55 (11th July 2017) - Hu, Changmin; Yu, Le; Wei, Mei
Abstract : Intrafibrillar silicified collagen fibrils are successfully fabricated using a one-step collagen self-assembly/silicification approach, which better support osteoblast activities. Abstract : Inspired by the silicification process in nature, intrafibrillar silicified collagen fibrils were successfully fabricated using a biomimetic one-step collagen self-assembly/silicification approach, in which collagen self-assembly and intrafibrillar silicification occurred simultaneously. To the best of our knowledge, it is the first time that intrafibrillar silicified collagen fibrils were formed via a one-step simultaneous approach, where collagen fibrils served as a templating matrix, and poly(allylamine) hydrochloride and sodium tripolyphosphate acted as the respective positive and negative analogs of zwitterionic proteins. By tailoring zwitterionic proteins analogs, silicified collagen fibrils with different microstructures, including core–shell, twisted and banded structures, were achieved. The intrafibrillar silicified collagen fibrils demonstrated significant improvement in osteoblast proliferation compared with apatite mineralized collagen fibrils. These findings open a new avenue for preparation of silicon-containing hierarchical biocomposites for biomedical needs.